Comparative Study of 2D Grid Antenna Array Geometries for Massive Array Systems - Gabillard,T; Sridhar,V; Manikas,A (IEEE, 2015)
In upcoming trends of wireless communications, such as massive MIMO, the number of antennas at the transmitter(TX) and receiver (RX) are expected to increase dramatically, aiming to provide a substantial improvement in system performance and spectral efficiency. However, an increase in the number of antennas also results in an increase in hardware, computational complexity and energy dissipation of the MIMO system. Therefore, the antenna array geometry plays a crucial role in the overall system performance. This paper is concerned with planar antenna array geometries with emphasis given to the family of 2D "grid" arrays and presents an insight into the relation between the array geometry and various performance metrics, such as detection, resolution and data-rate maximization, that may be used in different applications.